Correlation of Undercarboxylated Osteocalcin (ucOC) Concentration and Bone Density with Age in Healthy Korean Women - Kim, Sang-Man (The Korean Academy of Medical Sciences, 2010)
Uncarboxylated osteocalcin (ucOC) is important in evaluating vitamin K status and it is inversely associated with bone mineral density (BMD). We studied the correlationship between ucOC and BMD in healthy Korean women. This study recruited 337 healthy women between ages 20-70 were recruited. Serum ucOC, calcium, alkaline phosphatase, body mass index (BMI), and BMD were measured and compared. Mean BMI was lowest (20.3±1.9 kg/m(2)) in the 20 yr old group and highest (24.8±2.6 kg/m(2)) in the 60 yr old group. Women age 20-70 yr old had ucOC inversely related to BMD independent of other factors that may influence BMD. Serum ucOC concentration and BMD of lumbar spine showed a significant inverse relationship. Serum mean alkaline phosphatase was lowest (122±30 IU/L) in the age 30 group and highest (190.3±55.8 IU/L) in the age 60 group. Serum ucOC was inversely associated with BMI, and positively associated with alkaline phosphatase. Uncarboxylated osteocalcin (ucOC) was inversely associated with spinal BMD in healthy Korean women. Serum mean ucOC was highest in the age 20 group, followed by age 50 group, which may indicate vitamin K insufficiency could be related to high bone turnover in these groups. These results suggest that vitamin K supplement may be considered to help both bone growth and bone loss during these periods.